Тенденції формування рідномовного освітнього просторумігрантів у полілінгвальному середовищікраїн поселення - Романюк, Світлана (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The article focuses on the dynamics of modern emigration of Ukrainians and their adaptation in the flourishing environment of the countries of residence. It is noted that in order to preserve their national identity, they organized an extensive system of mother-tongue schooling (native schools, courses and schools of Ukrainian studies, Saturday and Sunday schools) where the Ukrainian language is taught.Found that today most schools with Ukrainian language operates in Brazil, Moldova, Transnistria and Romania. It has been found that it is compact settlement of immigrants contributing to the consolidation, preservation of national identity, providing opportunities for life and their educational needs. It is proved that in preserving national identity plays an important role Ukrainian native language, which laid the foundations of the family / household.The leading role in this process is played Saturday and Sunday schools that nurtured the cult of the mother tongue, ethnology, Ukrainian traditions. In the context of the activity analyze for example the London School Ukrainian Virgin Mary, which aims at educating Christian and patriotic spirit children of Ukrainian origin.The school instills pupils love for the Ukrainian language and culture, the desire to support national traditions. Focused on educational and methodological support, namely, the textbooks on which students study, indicated on their small numbers, analyzed bilingual programs and singled out cycle of academic disciplines that provide the formation and development of Ukrainian identity in the diaspora.
Keywords: immigrants; polylingual; mother tongue environment; native language; Ukrainian language; Saturday and Sunday schools; foreign Ukrainians; diaspora; country of settlement